Apakah Kunjungan Rumah oleh Kader Posyandu Meningkatkan Pengetahuan dan Persepsi Ibu Tentang Zero New Stunting? Does Home Visiting by Cadres Improve Maternal Knowledge and Perceptions of Zero New Stunting? - Tri Siswati; Joko Susilo; Yustiana Olfah; Bunga Astria Paramashanti; Jutharat Attawet; Idi Setiyobroto (Universitas Airlangga, 2025)
Background: Stunting remains a significant public health issue in Indonesia. Low knowledge and perception of mothers about nutrition, health, and the First 1000 Days of Life are determining factors. Objectives: To observe the impact of home visits on the knowledge and perception of maternal children about the Zero New Stunting (ZNS) program. Methods: This study employed a mixed-methods approach with a sequential explanatory design, conducted from June to August 2025 in Sumberadi Village, Sleman, Yogyakarta, Indonesia. The subjects were 35 stunted toddler pairs with mothers who met the inclusion criteria. Interventions are integrative nutrition education packages through home visits by trained Posyandu cadres, nutrition education (growth monitoring, developmental stimulation, and IYCF), and counseling. A structured questionnaire containing knowledge and perception questions of 25 questions each was used. The analysis was carried out using a t-test to see the differences before and after the intervention. Meanwhile, qualitative data were analyzed manually according to the theme of the interview. Results: The mean knowledge score increased from 61.2±9.8 (pre-test) to 86.4±7.1 (post-test 3), with a mean difference of 25.2 points (p-value<0.001). The perception score increased from 58.4±10.2 to 82.4±7.4, with an average difference of 24.0 points (p-value<0.001). Meanwhile, the results of qualitative findings showed high acceptance of the program, including increased self-efficacy, emotional support, and practical guidance during home visits. Conclusions: Home visits by cadres with integrated nutrition education effectively improve mothers’ knowledge and perceptions on stunting prevention, supporting the ZNS program.